Composite conductive film electrode for ultraviolet photoelectric device and preparation method of composite conductive film electrode

By spraying pyrolytic deposition of the pyrolytic acetylacetonate protective layer on the surface of the silver nanowire film, the problems of low transmittance and charge collection efficiency of the conductive films of existing ultraviolet photoelectric devices under short-wave ultraviolet light are solved, and higher responsiveness, signal stability and service life are achieved.

CN119816004AActive Publication Date: 2025-04-11CHONGQING UNIV OF ARTS & SCI
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510007826.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-11
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

The transparent conductive films of existing ultraviolet photoelectric devices have a low transmittance under short-wave ultraviolet light and low charge collection efficiency, resulting in low quantum efficiency, poor signal stability, and large noise and current, which affects the application prospects of the device.

Method used

The pyrolytic zirconium acetylacetonate is used as the protective layer, and a composite protective layer is formed on the surface of the silver nanowire film through spray pyrolytic deposition technology to improve the chemical stability and optical transmittance of the conductive film.

Benefits of technology

It significantly improves the responsiveness, signal stability and service life of ultraviolet photoelectric devices, reduces noise density, optimizes interface binding force, and ensures excellent light transmittance and charge collection ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816004A_ABST
    Figure CN119816004A_ABST
Patent Text Reader

Abstract

A transparent composite conductive film electrode used for an ultraviolet photoelectric device is composed of an electrode bottom layer and a top layer on the surface of the electrode bottom layer, the electrode bottom layer is a silver nanowire film, the top layer is a pyrolytic zirconium acetylacetonate protective layer, and the pyrolytic zirconium acetylacetonate protective layer is formed by using zirconium acetylacetonate as solute. The preparation method comprises the following steps: preparing a precursor solution by taking ethanol and dimethylformamide as a composite solvent, depositing the precursor solution on the surface of a silver nanowire film through atomization pyrolysis, and finally, performing vacuum annealing to obtain a pyrolysis zirconium acetylacetonate protective layer which is decomposed into complex components. According to the invention, zirconium acetylacetonate is dissolved in a composite solvent composed of DMF and ethanol, spray pyrolysis deposition is carried out on the surface of the Ag nanowire film to form the transparent conductive film, and the light transmittance of the conductive film under 310 nm ultraviolet light reaches 97.7% of that of an Ag nanowire film without a protective layer. The formed composite electrode effectively improves the charge collection capability and transmission stability of the electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductive film preparation, and in particular to a composite conductive film electrode for ultraviolet photoelectric devices and a preparation method thereof. Background Art

[0002] Sensors, also called sensors or detectors, are instruments that collect, detect and record electromagnetic radiation information from objects. Structurally, all types of sensors are composed of collectors, detectors, processors and output devices, so sensors are often called detectors, that is, detectors are a type of sensor, and detectors can be classified into ultraviolet detectors, visible light detectors, infrared detectors, etc. according to the detection wavelength. Ultraviolet photoelectric devices include ultraviolet photodetectors, ultraviolet light-emitting diodes, etc. Ultraviolet photoelectric thin film diode detectors have broad application prospects in medical imaging, missile identification and tracking, communications, environmental and biochemical detection, etc. due to their high sensitivity, high resolution, and rapid response. Ultraviolet photoelectric devices are generally composed of bottom electrodes, p-type semiconductor films, n-type semiconductor films, and transparent conductive films deposited and stacked in sequence. Ultraviolet photoelectric devices have special requirements for transparent conductive films, which need to have high ultraviolet transmittance, excellent physical and chemical stability, and resistance to ultraviolet damage. They are key materials for ultraviolet photoelectric devices.

[0003] Existing transparent conductive films such as indium tin oxide (ITO), fluorine-doped tin oxide (FTO), and aluminum-doped zinc oxide (AZO) have low transmittance to short-wave ultraviolet rays. For example, the average transmittance of ITO in the UVB range (280-320 nm) is about 25%. Therefore, the photoelectric conversion efficiency of optical devices based on ITO windows in the UVB region is very low, which seriously restricts its application. Therefore, it is difficult to use it as a UV window electrode for deep ultraviolet detection. In the prior art, it is reported that silver nanowires (AgNws) are used as window electrodes for ultraviolet photoelectric devices, but the contact between the electrode and other films is loose physical contact, and the charge collection efficiency is not high, resulting in low quantum efficiency of the device. In addition, nanomaterials have poor chemical stability and poor interface contact, especially photodetectors, which have poor signal stability and large noise current, which is not conducive to subsequent signal amplification processing. In addition, the influence of the external environment causes the film resistance to change, the signal repeatability is poor, and the service life of some devices decreases rapidly. Summary of the invention

[0004] Based on the above technical problems, the present invention aims to provide an ultraviolet window electrode for ultraviolet photoelectric devices. When the electrode is used in ultraviolet photoelectric thin film detectors, the responsiveness, signal stability and service life are significantly improved, while the noise density is reduced, which is beneficial to the subsequent signal amplification processing.

[0005] Another object of the present invention is to provide a method for preparing the above-mentioned ultraviolet window electrode. The ultraviolet window electrode prepared by the method has high transparency, excellent conductivity, and strong adhesion and water and oxygen resistance on the surface of ultraviolet photoelectric materials.

[0006] The purpose of the present invention is achieved through the following technical solutions: A transparent composite conductive film electrode for optoelectronic devices, characterized in that: the transparent conductive film is a silver nanowire film protected by pyrolytic zirconium acetylacetonate, specifically composed of an electrode bottom layer and a top layer on its surface, the electrode bottom layer is the silver nanowire film, the top layer is pyrolytic zirconium acetylacetonate, the pyrolytic zirconium acetylacetonate is a precursor solution prepared with zirconium acetylacetonate as a solute and ethanol and dimethylformamide as a composite solvent, deposited on the surface of the silver nanowire film by atomization pyrolysis, and finally vacuum annealed to obtain the pyrolytic zirconium acetylacetonate decomposed into complex components.

[0007] Furthermore, in the composite solvent, the volume ratio of ethanol to dimethylformamide is 3:1 to 5:1.

[0008] Furthermore, the concentration of the mixed solution is 0.006-0.05 mol / L.

[0009] Furthermore, the pyrolytic deposition temperature of pyrolytic zirconium acetylacetonate is 110~140 ℃, and the deposition rate is 2~10 nm / min.

[0010] Furthermore, the atomizer for spray pyrolysis uses a 1.4 MHz ultrasonic atomization head, the diameter of the mist guide tube outlet is 20 mm, the distance between the mist guide tube outlet and the sample is 10-20 mm, the carrier gas is nitrogen, the rate is 6-10 L / min, and the atomization rate is about 3-15 mL / min.

[0011] Furthermore, the vacuum annealing is performed at 140-200° C. for 0.5-24 h, preferably in a vacuum tube furnace, in order to assist in increasing the degree of decomposition of zirconium acetylacetonate.

[0012] A preparation method for a composite conductive film electrode, characterized in that: zirconium acetylacetonate is used as a raw material to prepare a drive liquid, the precursor liquid is sprayed and pyrolyzed and deposited on the surface of a silver nanowire film to form a pyrolyzed zirconium acetylacetonate protective layer, the solvent of the precursor liquid is ethanol and dimethylformamide in a volume ratio of 3:1 to 5:1, and the concentration of the precursor liquid is 0.006 to 0.05 mol / L.

[0013] Furthermore, the spray pyrolysis atomizer adopts a 1.4 MHz ultrasonic atomization head, the diameter of the mist guide pipe outlet is 20 mm, the distance between the mist guide pipe outlet and the sample is 10-20 mm, the carrier gas is nitrogen, the introduction rate is 6-10 L / min, and the atomization rate is about 3-15 mL / min.

[0014] Furthermore, the pyrolysis deposition temperature is 110-140° C., the deposition rate is 2-10 nm / min, and the deposition thickness is 20-100 nm.

[0015] Furthermore, after the deposition, an annealing treatment is performed, the annealing vacuum is below 5 Pa, the annealing temperature is 140~200°C, and the annealing time is 0.5~24 h.

[0016] When silver nanowire (AgNws) films are used as window electrodes for UV optoelectronic devices, the charge collection efficiency is low, resulting in low quantum efficiency of the device. In addition, nanomaterials have poor chemical stability, especially for photodetectors, which have poor signal stability and large noise current, which is not conducive to subsequent signal amplification processing.

[0017] In the present invention, zirconium acetylacetonate is used as a raw material, dissolved in a composite solvent composed of ethanol and dimethylformamide to form a precursor solution, and deposited on the surface of the silver nanowire film by spray pyrolysis to form a protective layer. During the pyrolysis deposition process, by adjusting the deposition temperature at 110-140°C, the zirconium acetylacetonate solution is volatilized, initially pyrolyzed and solidified, and the initial formation of the protective layer forms protection for AgNws, and then vacuum annealing is performed at a higher temperature of 140-200°C to achieve further pyrolysis of the zirconium acetylacetonate. At this time, due to the initial protective effect of the protective layer, the higher annealing temperature will not damage the AgNws, thereby improving the chemical stability and optical transmittance of the transparent conductive film.

[0018] In the present invention, DMF and ethanol are used in a specific ratio to form a solvent to form a precursor solution. During the deposition and annealing process, the components and grain structure of the final pyrolyzed zirconium acetylacetonate are significantly affected. Under the specific pyrolysis deposition and annealing effects, the precursor solution has different volatilization characteristics at different temperatures, so that the pyrolysis of zirconium acetylacetonate forms a complex decomposition and crystallization process, and generates a protective layer with a unique grain structure whose components are between zirconium acetylacetonate and zirconium oxide. The protective layer film is attached to the AgNws film to form a dense structure with uniform distribution of various components, which effectively improves the signal stability of the transparent conductive film and reduces the noise current density.

[0019] A method for preparing a composite conductive film electrode, characterized in that it comprises the following steps: S1. Preparation of AgNws thin films Silver nanowire ink with a solid content of 8-12 g / L and a diameter of 25-35 nm was used to deposit a thin film on the substrate surface, and then annealed at 100 °C for 10 min to prepare a silver nanowire film with a thickness of 30-40 nm and a square resistance of 10-12 Ω / sq. S2. Preparation of mixed solution Zirconium acetylacetonate is added to a composite solvent consisting of ethanol and dimethylformamide to prepare a mixed solution with a concentration of 0.006-0.05 mol / L, wherein the volume ratio of ethanol to dimethylformamide in the composite solvent is 3:1-5:1; S3. Spray pyrolysis deposition of top layer The AgNws film was heated to 110-140 °C, the mixed solution prepared in step S1 was placed in a nebulizer cup, and a 1.4 MHz ultrasonic atomizer was used for atomization. The mist was directed to the surface of the AgNws film through a mist guide tube. The diameter of the mist guide tube outlet was 20 mm, and the distance between the outlet and the sample was 10-20 mm. Nitrogen was used as a carrier gas at a rate of 6-10 L / min, an atomization rate of about 3-15 mL / min, and a deposition rate of pyrolytic zirconium acetylacetonate was 2-10 nm / min, with a deposition thickness of 20-100 nm. S4. Annealing The film was annealed in a vacuum tube furnace with a vacuum degree below 5 Pa, an annealing temperature of 140-200 °C, and an annealing time of 0.5-24 h.

[0020] The present invention has the following technical effects: The invention dissolves zirconium acetylacetonate in a composite solvent consisting of DMF and ethanol, deposits the mixture on the surface of a Ag nanowire film by spray pyrolysis, and forms a multi-component complex system protective layer between zirconium acetylacetonate and zirconium oxide after pyrolysis, thereby solving the problems in the prior art of low bonding between the film prepared by AgNws and the detection material and loose interface bonding, optimizing the interface bonding, and ensuring excellent light transmittance. The transmittance of 310nm ultraviolet light reaches 97.7% of that of the Ag nanowire film without a protective layer, and the formed composite electrode effectively improves the charge collection capability and transmission stability of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 : Schematic diagram of the ultrasonic spray pyrolysis device used for depositing and pyrolyzing zirconium acetylacetonate of the present invention.

[0022] Figure 2 : Thermal analysis diagram of zirconium acetylacetonate.

[0023] Figure 3 : X-ray photoelectron spectroscopy (XPS) of pyrolyzed zirconium acetylacetonate prepared at different temperatures.

[0024] Figure 4 : Comparison of scanning electron microscope photos of the transparent conductive film for ultraviolet optoelectronic devices prepared in Example 1 of the present invention and the unprotected AgNws film.

[0025] Figure 5: Light transmittance test diagram of the transparent conductive film for ultraviolet optoelectronic device prepared in Example 1 of the present invention and Comparative Example 1.

[0026] Figure 6 : The transparent conductive film for the ultraviolet optoelectronic device prepared in Example 1 of the present invention was tested and compared with the unprotected AgNws film tape.

[0027] Figure 7 : Comparison of the IT response characteristic curves of the detector prepared by Example 2 of the present invention and the control group without a protective layer to ultraviolet light of different bands.

[0028] Figure 8 : Comparison of the photocurrent changes over time of the detector prepared in Example 2 of the present invention and the control detector without a protective layer.

[0029] Fig. 9 : A comparison diagram of noise current density between the detector prepared in Example 2 of the present invention and a control detector without a protective layer.

[0030] Fig.10 : Comparison of the responsivity of detectors with protective layers of different thicknesses prepared in Example 2 of the present invention and Comparative Example 2 to 310 nm ultraviolet light. DETAILED DESCRIPTION

[0031] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above-mentioned contents of the present invention.

[0032] Example 1 A method for preparing a composite conductive film electrode comprises the following steps: S1. Preparation of AgNws thin films Silver nanowire ink with a solid content of 10 g / L and a diameter of 25-35 nm was used to deposit a thin film on the substrate surface, and then annealed at 100 °C for 10 min to prepare a silver nanowire film with a thickness of 30 nm and a square resistance of 10 Ω / sq. S2. Preparation of mixed solution Zirconium acetylacetonate is added to a composite solvent composed of ethanol and dimethylformamide to prepare a mixed solution with a concentration of 0.01 mol / L, wherein the volume ratio of ethanol to dimethylformamide in the composite solvent is 4:1; S3. Spray pyrolysis deposition of top layer The AgNws film was heated to 120 °C, and the mixed solution prepared in step S1 was placed in a nebulizer cup. A 1.4 MHz ultrasonic atomizer was used for atomization. The mist was directed to the surface of the AgNws film through a mist guide tube. The diameter of the mist guide tube outlet was 20 mm, and the distance between the outlet and the sample was 15 mm. Nitrogen was used as a carrier gas at a rate of 8 L / min, an atomization rate of 12 mL / min, a pyrolytic zirconium acetylacetonate deposition rate of 5 nm / min, and a deposition thickness of 50 nm. S4. Annealing The film was annealed in a vacuum tube furnace with a vacuum degree below 5 Pa, an annealing temperature of 160 °C, and an annealing time of 24 h.

[0033] Figure 1 The figure is a schematic diagram of the ultrasonic spray pyrolysis device used for depositing and pyrolyzing zirconium acetylacetonate according to the present invention.

[0034] Figure 2 The figure is a thermal analysis diagram of zirconium acetylacetonate, from which it can be seen that the weight loss interval starting from 101°C is the first stage of thermal decomposition, the interval starting from 264°C is the second stage of decomposition of zirconium acetylacetonate, and zirconium acetylacetonate is not completely decomposed into zirconium oxide before 500°C. In the present invention, the thermal decomposition temperature and annealing temperature of zirconium acetylacetonate are 110-140°C and 140-200°C, respectively, indicating that the prepared protective layer is not a simple zirconium oxide or zirconium acetylacetonate, but a complex component system composed of multiple decomposition components.

[0035] Figure 3 The X-ray photoelectron spectra (XPS) of pyrolyzed zirconium acetylacetonate prepared at different temperatures. Among them, the peak with larger binding energy is the O1s XPS peak in acetylacetonate (acac), and the peak with smaller binding energy is the O1s XPS peak in zirconium oxide. As the pyrolysis temperature increases from 120 ℃ to 200 ℃, the O1s XPS peak in zirconium oxide gradually increases, but the O1s XPS peak in acetylacetonate (acac) is still dominant, further confirming that the protective layer is an intermediate product between zirconium acetylacetonate and zirconium oxide.

[0036] Figure 4 This is a scanning electron microscope photo of the AgNws transparent conductive film with pyrolytic zirconium acetylacetonate protective layer prepared in Example 1 of the present invention, where a is an unprotected AgNws film electrode and b is an ultraviolet window electrode with a pyrolytic zirconium acetylacetonate protective layer deposited on the surface. It can be seen from the figure that the AgNWs are covered in the pyrolytic zirconium acetylacetonate protective layer, the surface is dense, and no cracks or holes are observed.

[0037] Comparative Example 1 In order to reflect the advantages of pyrolytic zirconium acetylacetonate, hafnium acetylacetonate with similar properties was used to replace the zirconium acetylacetonate in the precursor solution, and pyrolytic hafnium acetylacetonate protected AgNws films of different thicknesses were prepared on quartz glass and compared with AgNws films of different thicknesses protected by pyrolytic zirconium acetylacetonate prepared by the method of Example 1.

[0038] The ultraviolet light transmittance of the conductive films prepared in Example 1 and Comparative Example 1 was tested. The results are as follows: Figure 5 As shown in the figure, it can be seen that the pyrolytic hafnium acetylacetonate has an obvious absorption peak in the range of 240-330 nm. When the thickness is low, the effect on the transmittance of the transparent conductive film is low, but when the thickness of the pyrolytic hafnium acetylacetonate is large, the effect is obvious. For example, when the thickness of the pyrolytic hafnium acetylacetonate increases from 20nm to 60nm, the transmittance of the transparent conductive film at 310nm decreases from 64% to 30%, and the device performance is significantly reduced. Among the AgNws films protected by pyrolytic zirconium acetylacetonate, the 20 nm thick pyrolytic zirconium acetylacetonate protected AgNws transparent conductive film (green) has good transmittance in the entire UV region (85% transmittance at 310 nm), which is close to the AgNws film without a protective layer (87% transmittance at 310 nm). As the thickness of the pyrolytic zirconium acetylacetonate protective layer increases, the UV transmittance decreases slightly, but not significantly. For example, when the thickness of the pyrolytic zirconium acetylacetonate is 60 nm, the transmittance of the transparent conductive film only decreases from 85% to 82%, which has little effect on the device performance. This shows that the coverage of the protective layer has little effect on the UV transmittance of the electrode.

[0039] Figure 6 The results of the tape test of AgNws transparent conductive film protected by pyrolytic zirconium acetylacetonate and unprotected AgNws film. The AgNws film protected by pyrolytic zirconium acetylacetonate did not fall off the substrate, and the square resistance did not change significantly, indicating that the AgNws transparent conductive film with pyrolytic zirconium acetylacetonate protective layer has good adhesion strength, while the unprotected AgNws film is very easy to be removed by the tape. In addition, the AgNws transparent conductive film protected by pyrolytic zirconium acetylacetonate does not absorb moisture or deliquesce in the air, and has good environmental stability. This shows that the AgNws transparent conductive film protected by pyrolytic zirconium acetylacetonate can improve the operability of ultraviolet optoelectronic devices.

[0040] Example 2 Apply the above preparation method to the ultraviolet photodiode detector: With the size of 2×3 cm 2, ITO glass with a square resistance of 6Ω was used as the substrate, one side of which was covered with a small area of ​​polyimide high-temperature resistant tape, and TiO2 precursor was spin-coated on the ITO glass, and then annealed at 460 ℃ for 30 min to obtain a TiO2 film with a thickness of 20 nm; then Bi2O3 precursor was spin-coated on the surface of the TiO2 film, and after the spin coating was completed, it was annealed at 450 ℃ for 30 min to prepare a Bi2O3 film with a thickness of about 40 nm; then NiO precursor was spin-coated on the surface of the Bi2O3 film, and annealed at 400 ℃ for 20 min to prepare a NiO film with a thickness of 20 nm.

[0041] A layer of AgNws transparent conductive film protected by pyrolyzed zirconium acetylacetonate was prepared on the surface of the substrate deposited with ITO / TiO2 / Bi2O3 / NiO according to the method of Example 1. Finally, the polyimide high temperature resistant tape was peeled off, and the electrode pins were made of silver glue in the electrode film and the blank area of ​​ITO to obtain a complete ultraviolet photodiode detector.

[0042] Figure 7 The graphs show the IT response characteristics of the detectors prepared by Example 1 of the present invention and the control group without the protection of the AgNws conductive film by pyrolytic acetylacetonate zirconium layer to ultraviolet light of different bands. Compared with the pure AgNws electrode, the detection performance of the AgNws transparent conductive film protected by pyrolytic acetylacetonate zirconium layer is improved to varying degrees in the 254-365nm band. For example, at a power density of 5 μWcm -2 Under 254 nm ultraviolet light, the detector photocurrent of the AgNws transparent conductive film protected by pyrolyzed zirconium acetylacetonate is 0.84 μA, which is higher than the 0.65 μA of the detector with a simple AgNws electrode. The reason is that the pyrolyzed zirconium acetylacetonate increases the binding of AgNws in the AgNws transparent conductive film with the pyrolyzed zirconium acetylacetonate protective layer to the detector film surface, reducing the contact resistance between AgNws and NiO. In comparison, pure AgNws adhere to the NiO surface by physical contact, with weak adhesion and poor contact tightness, resulting in reduced charge transfer and collection efficiency.

[0043] Figure 8 The photocurrent of the detector of the present invention is compared with that of the detector without AgNws UV window electrode protection over time. It can be seen from the figure that the performance of the detector with pyrolyzed zirconium acetylacetonate protecting AgNws transparent conductive film remains stable after being placed in the environment for 90 days. -2Under 254 nm ultraviolet light, the photocurrent remains almost constant at 0.84-0.80 μA. However, the detector using a pure AgNws ultraviolet window electrode showed obvious attenuation due to the gradual oxidation of AgNws in the environment. Under the same conditions, the photocurrent dropped rapidly from 0.65 μA to 0.38 μA within one month, and further dropped to 0.26 μA after three months. Pyrolysis of zirconium acetylacetonate can also reduce the noise current of the ultraviolet detector. Fig. 9 As can be seen from the figure, the detector is protected by pyrolyzed zirconium acetylacetonate as the window electrode. -3 The noise current density in the frequency range of Hz-50Hz is significantly reduced, which indicates that the detector has a better gain effect when amplifying the signal.

[0044] Comparative Example 2 According to the preparation of Example 2, the AgNws transparent conductive film was replaced with a protection film of pyrolyzed hafnium acetylacetonate, and the effects of pyrolyzed hafnium acetylacetonate and pyrolyzed zirconium acetylacetonate of different thicknesses on the response performance of the ultraviolet detector were tested.

[0045] The results are as follows Fig.10 As shown in Figure 2, the device with unprotected AgNWs transparent conductive film as the window has a responsivity of 0.135 AW at 254 nm. -1 When the protective layer thickness is 20 nm, the performance of the two devices is close, and both are significantly improved compared to the unprotected ones. When the thickness exceeds 30 nm, the device responsiveness of the device with pyrolyzed zirconium acetylacetonate protected AgNWs transparent conductive film as the window electrode is significantly higher than that of the device with pyrolyzed hafnium acetylacetonate protected AgNWs transparent conductive film as the window, and the responsiveness is 0.167 AW -1 and 0.148 AW -1 As the thickness of the protective layer increases, the performance gap becomes larger and larger. The thickness of the pyrolyzed hafnium acetylacetonate has a greater impact on the photoresponse of 310nm ultraviolet light. The device with unprotected AgNWs transparent conductive film as the window has a photoresponse of 0.064 AW at 310 nm. -1 When the protective layer thickness is 20 nm, the performance difference between the devices using AgNWs transparent conductive films protected by pyrolytic zirconium acetylacetonate and pyrolytic hafnium acetylacetonate as window electrodes is not obvious, and the responsivity is 0.088 AW -1 and 0.082 AW -1 However, when the thickness of the protective layer is 80nm, the responsiveness of the device with pyrolytic acetylacetonate zirconium protecting AgNWs transparent conductive film as the window and the device with pyrolytic acetylacetonate hafnium protecting AgNWs transparent conductive film as the window to 310nm ultraviolet light is 0.082AW -1 and 0.046 AW -1, indicating that pyrolyzed zirconium acetylacetonate as a protective layer of AgNWs is more advantageous when the thickness is larger, and is more conducive to improving the stability and repeatability of device performance in industrial production.

[0046] During the preparation process, the precursor mixture prepared by zirconium acetylacetonate in different solvents had obvious differences in the effect on the electrode performance after preparing a 50 nm thick protective layer on the surface of the AgNws film. The results are shown in Table 1.

[0047] Table 1:

[0048] It can be seen that after 90 days, the light transmittance of the conductive film with a protective layer prepared with DMF and ethanol as the composite solvent was basically unchanged at 240-330nm, while the light transmittance of the composite solvent groups of ethanol alone and ethanol and ethylene glycol methyl ether decreased significantly. -2 Under the conditions of 100 ℃ and 200 ℃, the photocurrent of the composite solvent group of DMF and ethanol was still relatively stable after 90 days, while the single ethanol and ethanol and ethylene glycol methyl ether groups showed obvious attenuation. It can be seen that different solvent selections have different effects on the structure and performance of the formed protective layer. The composite solvent composed of DMF and ethanol in the present invention effectively improves the structural and performance stability of the film.

[0049] Example 3 A method for preparing a composite conductive film electrode comprises the following steps: S1. Preparation of AgNws thin films Silver nanowire ink with a solid content of 8 g / L and a diameter of 25-35 nm was used to deposit a thin film on the substrate surface, and then annealed at 100 °C for 10 min to prepare a silver nanowire film with a thickness of 40 nm and a square resistance of 12 Ω / sq. S2. Preparation of mixed solution Zirconium acetylacetonate is added to a composite solvent composed of ethanol and dimethylformamide to prepare a mixed solution with a concentration of 0.05 mol / L, wherein the volume ratio of ethanol to dimethylformamide in the composite solvent is 3:1; S3. Spray pyrolysis deposition of top layer The AgNws film was heated to 140 °C, and the mixed solution prepared in step S1 was placed in a nebulizer cup. A 1.4 MHz ultrasonic atomizer was used for atomization. The mist was directed to the surface of the AgNws film through a mist guide tube. The diameter of the mist guide tube outlet was 20 mm, and the distance between the outlet and the sample was 20 mm. Nitrogen was used as a carrier gas at a rate of 6 L / min. The atomization rate was about 3 mL / min, the deposition rate of pyrolytic zirconium acetylacetonate was 10 nm / min, and the deposition thickness was 100 nm. S4. Annealing The film was annealed in a vacuum tube furnace with a vacuum degree below 5 Pa, an annealing temperature of 200 °C, and an annealing time of 0.5 h.

[0050] The 100 nm thick AgNws transparent conductive film protected by pyrolyzed zirconium acetylacetonate prepared in this embodiment has good transmittance in the entire ultraviolet region, with a transmittance of 81% at 310 nm; the device with the transparent conductive film as a window has a response of 0.078 AW to 310 nm ultraviolet light. -1 .

[0051] Example 4 A method for preparing a composite conductive film electrode comprises the following steps: S1. Preparation of AgNws thin films Silver nanowire ink with a solid content of 12 g / L and a diameter of 25-35 nm was used to deposit a thin film on the substrate surface, and then annealed at 100 °C for 10 min to prepare a silver nanowire film with a thickness of 35 nm and a square resistance of 10 Ω / sq. S2. Preparation of mixed solution Zirconium acetylacetonate was added into a composite solvent consisting of ethanol and dimethylformamide to prepare a mixed solution with a concentration of 0.006 mol / L, wherein the volume ratio of ethanol to dimethylformamide in the composite solvent was 5:1; S3. Spray pyrolysis deposition of top layer The AgNws film was heated to 110 °C, and the mixed solution prepared in step S1 was placed in a nebulizer cup. A 1.4 MHz ultrasonic atomizer was used for atomization. The mist was directed to the surface of the AgNws film through a mist guide tube. The diameter of the mist guide tube outlet was 20 mm, and the distance between the outlet and the sample was 10 mm. Nitrogen was used as a carrier gas at a rate of 10 L / min. The atomization rate was about 15 mL / min, the deposition rate of pyrolytic zirconium acetylacetonate was 2 nm / min, and the deposition thickness was 20 nm. S4. Annealing The film was annealed in a vacuum tube furnace with a vacuum degree below 5 Pa, an annealing temperature of 140 °C, and an annealing time of 10 h.

[0052] The 20 nm thick AgNws transparent conductive film protected by pyrolyzed zirconium acetylacetonate prepared in this embodiment has good transmittance in the entire ultraviolet region, with a transmittance of 86% at 310 nm; the device with the transparent conductive film as a window has a response of 0.085 AW to 310 nm ultraviolet light. -1 .

Claims

1. A transparent composite conductive film electrode for ultraviolet optoelectronic devices, characterized in that: The transparent conductive film is composed of an electrode bottom layer and a top layer on its surface. The electrode bottom layer is a silver nanowire film, and the top layer is a pyrolytic zirconium acetylacetonate protective layer. The pyrolytic zirconium acetylacetonate protective layer is a precursor solution prepared by using zirconium acetylacetonate as a solute and ethanol and dimethylformamide as a composite solvent. The precursor solution is deposited on the surface of the silver nanowire film through atomization pyrolysis, and finally vacuum annealing is performed to obtain the pyrolytic zirconium acetylacetonate protective layer decomposed into complex components.

2. A transparent composite conductive film electrode for ultraviolet optoelectronic devices according to claim 1, characterized in that: In the composite solvent, the volume ratio of ethanol to dimethylformamide is 3:1-5:

1.

3. A transparent composite conductive film electrode for ultraviolet optoelectronic devices as claimed in claim 1 or 2, characterized in that: The pyrolytic deposition temperature of pyrolytic zirconium acetylacetonate is 110~140 ℃, and the deposition rate is 2~10 nm / min.

4. A transparent composite conductive film electrode for ultraviolet optoelectronic devices according to any one of claims 1 to 3, characterized in that: The vacuum annealing is performed at 140-200°C for 0.5-24 h, preferably in a vacuum tube furnace.

5. A method for preparing a composite conductive film electrode, characterized in that: The method uses zirconium acetylacetonate as a raw material to prepare a driving liquid, sprays the precursor liquid for pyrolysis and deposition on the surface of a silver nanowire film to form a pyrolyzed zirconium acetylacetonate protective layer, wherein the solvent of the precursor liquid is ethanol and dimethylformamide in a volume ratio of 3:1 to 5:1, and the concentration of the precursor liquid is 0.006 to 0.05 mol / L.

6. The method for preparing a composite conductive film electrode according to claim 5, characterized in that: The spray pyrolysis atomizer adopts a 1.4 MHz ultrasonic atomization head, the diameter of the mist guide pipe outlet is 20 mm, the distance between the mist guide pipe outlet and the sample is 10-20 mm, the carrier gas is nitrogen, the introduction rate is 6-10 L / min, and the atomization rate is about 3-15 mL / min.

7. The method for preparing a composite conductive film electrode according to claim 5 or 6, characterized in that: The pyrolysis deposition temperature is 110-140°C, the deposition rate is 2-10 nm / min, and the deposition thickness is 20-100 nm.

8. A method for preparing a composite conductive film electrode according to any one of claims 5 to 7, characterized in that: After deposition, annealing treatment is performed with an annealing vacuum degree below 5 Pa, an annealing temperature of 140-200 °C, and an annealing time of 0.5-24 h.

9. A method for preparing a composite conductive film electrode, characterized in that: The steps include: S1. Preparation of AgNws thin films Silver nanowire ink with a solid content of 8-12 g / L and a diameter of 25-35 nm was used to deposit a thin film on the substrate surface, and then annealed at 100 °C for 10 min to prepare a silver nanowire film with a thickness of 30-40 nm and a square resistance of 10-12 Ω / sq. S2. Preparation of mixed solution Zirconium acetylacetonate is added to a composite solvent composed of ethanol and dimethylformamide to prepare a mixed solution with a concentration of 0.006-0.05 mol / L, wherein the volume ratio of ethanol to dimethylformamide in the composite solvent is 3:1-5:1; S3. Spray pyrolysis deposition of top layer The AgNws film was heated to 110-140 °C, the mixed solution prepared in step S1 was placed in a nebulizer cup, and a 1.4 MHz ultrasonic atomizer was used for atomization. The mist was directed to the surface of the AgNws film by a mist guide tube. The diameter of the mist guide tube outlet was 20 mm, and the distance between the outlet and the sample was 10-20 mm. Nitrogen was used as a carrier gas at a rate of 6-10 L / min, and the atomization rate was about 3-15 mL / min. The deposition rate of pyrolytic zirconium acetylacetonate was 2-10 nm / min, and the deposition thickness was 20-100 nm. S4. Annealing The film was annealed in a vacuum tube furnace with a vacuum degree below 5 Pa, an annealing temperature of 140-200 °C, and an annealing time of 0.5-24 h.

Citation Information

Patent Citations

  • High-temperature superconducting nanometer composite film and method for preparing same

    CN101747031A

  • Method for manufacturing high-k dielectric layer water-based indium oxide thin film transistors

    CN104009093A

  • Method for directly preparing metal oxide / silver nanowire composite conductive network

    CN104575864A

  • Zirconia insulation film and preparation method thereof

    CN104599947A

  • Method for preparing flexible solar cell based on transparent composite conductive film

    CN110416417A